2019
DOI: 10.1177/1082013219883465
|View full text |Cite
|
Sign up to set email alerts
|

Grapefruit essential oils inhibit quorum sensing of Pseudomonas aeruginosa

Abstract: Citrus essential oils are used in food to confer flavor and aromas. The citrus essential oils have been granted as GRAS and could be used as antimicrobial additives to control bacterial quorum sensing from potential food bacterial pathogens. The chemical composition and inhibitory activity of Citrus paradisi (grapefruit) essential oils obtained by cold-pressed method (EOP) and cold-pressed method followed by steam distillation, against Pseudomonas aeruginosa were determined . The GC-MS analyses of the oil indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 36 publications
4
11
0
1
Order By: Relevance
“…It has been said that P. aeruginosa biofilm is more challenging to control than L. monocytogenes and S. aureus biofilm because the outer membrane of the Gram-negative bacteria could act as a barrier that prevents CEO penetration [ 26 ]. However, in line with the present results, Citrus paradisi (grapefruit) and Citrus reticulata (mandarin) essential oils were able to inhibit P. aeruginosa biofilm formation and the biofilm metabolic activity [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…It has been said that P. aeruginosa biofilm is more challenging to control than L. monocytogenes and S. aureus biofilm because the outer membrane of the Gram-negative bacteria could act as a barrier that prevents CEO penetration [ 26 ]. However, in line with the present results, Citrus paradisi (grapefruit) and Citrus reticulata (mandarin) essential oils were able to inhibit P. aeruginosa biofilm formation and the biofilm metabolic activity [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 87%
“…It was previously reported that some essential oils could interfere with the QS system regulation and the formation of virulence factors [ 31 , 32 ]. In line with this, the autoinducer production decreased between 26 and 55% in the lemon essential oils assayed; this result is similar to that found in grapefruit and mandarin essential oils [ 19 , 20 ]. Moreover, it was informed that Citrus extracts also decreased autoinducer production by about 90%, measured by a bioluminescence assay using Vibrio harveyi [ 33 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The effectiveness of C. paradisi EO against fungi: A. niger , A. flavus , C. albicans , Penicillium chrysogenum , Fusarium moniliforme and Saccharomyces cerevisiae has been confirmed [ 76 ]. According to Luciardi et al 2019 [ 77 ], grapefruit essential oils could be used as a food preservative to control P. aeruginosa virulence.…”
Section: Composition and Biological Activity Of Essential Oilsmentioning
confidence: 99%